Contribution of Digital Learning Object “Futsal RIVED” in de Processo of Teaching and Physical Education - Bavaresco, Ana Paola; Muller, Liziany Medeiros; Rech, Aline Pereira de Arruda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This study aims to evaluate the contribution of a digital learning object (ODA) in the teaching and learning process of students of Physical Education. The methodology used was a qualitative research with action. The ODA used was "Futsal RIVED" which presents a pedagogical proposal for teaching the fundaments of soccer. It was held the interactivity and exploration of ODA individually and in groups where it was analyzed, discussed, explored according to the proposed goals. It is concluded that the technologies applied in education as teaching resources acquire functions to help in the teaching-learning process bringing new views and different ways of learning.